2021
DOI: 10.4103/aja.aja_53_20
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ECOG performance status and Gleason score in the survival of castration-resistant prostate cancer

Abstract: Eastern Cooperative Oncology Group (ECOG) performance status and Gleason score are commonly investigated factors for overall survival (OS) in men with castration-resistant prostate cancer (CRPC). However, there is a lack of consistency regarding their prognostic or predictive value for OS. Therefore, we performed this meta-analysis to assess the associations of ECOG performance status and Gleason score with OS in CRPC patients and compare the two markers in patients under different treatment regimens or with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…Because of the concomitant use with prednisolone, the mineralocorticoid effect might have caused adverse events in the abiraterone group 24 . Even though serious adverse events, e.g., seizure and febrile neutropenia from enzalutamide or tachycardia and transaminitis form abiraterone were reported, none of those were presented in this study 6,24,27 . All adverse events were grades 1 to 2 and did not lead to treatment withdrawal.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Because of the concomitant use with prednisolone, the mineralocorticoid effect might have caused adverse events in the abiraterone group 24 . Even though serious adverse events, e.g., seizure and febrile neutropenia from enzalutamide or tachycardia and transaminitis form abiraterone were reported, none of those were presented in this study 6,24,27 . All adverse events were grades 1 to 2 and did not lead to treatment withdrawal.…”
Section: Discussionmentioning
confidence: 60%
“…The related study demonstrated the potential predictive value of ECOG (ECOG ≥2 vs <2) for OS among patients with metastatic prostate cancer 27 . A significant difference between ECOG score of 0 and 1 to 2 on OS and PFS was not found 28 .…”
Section: Discussionmentioning
confidence: 88%
“…The main reason was imbalance in disease severity between the two groups, particularly in terms of performance status and self-care ability (e.g., ECOG score), which would have led to a substantial selection bias in the prognostic analysis. ECOG score was considered to be a significant prognostic factor in castration-resistant prostate cancer ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the Gleason pattern 5, prostate cancer with a Gleason score 9–10 is indicative of particularly aggressive disease 20–22 . PS as a prognostic factor for OS has been evaluated in men with CRPC 23 . Furthermore, several recent investigators have advocated that anemia is a powerful prognostic factor in PC 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 , 22 PS as a prognostic factor for OS has been evaluated in men with CRPC. 23 Furthermore, several recent investigators have advocated that anemia is a powerful prognostic factor in PC. 24 , 25 In particular, Okamoto et al .…”
Section: Discussionmentioning
confidence: 99%